RETRACTED: The Role of Subject in Kuntowijoyo's Transformative Thought and It's Relevance to The Islamic Social Transformation - Khasri, Muhammad Rodinal Khair (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Filsafat to article entitled â€œThe Role of Subject in Kuntowijoyo's Transformative Thought and It's Relevance to The Islamic Social Transformationâ€ Vol 30, No 2, pp. 261-286, 2020, DOI:Â https://doi.org/10.22146/jf.54911Â This paper has been found to be in violation of the Jurnal Filsafat Publication principles and will be retracted.The article contained redundant material, the editor investigated and found that the paper published inÂ â€œThe Role of Subjects in Kuntowijoyo's Transformative Thought and It's Relevance to the Prophetical Social Transformationâ€ Vol 4, No 2, pp.Â 126-144, August 2020, DOI:Â 10.22146/sasdayajournal.59662The document and its content will be removed from Jurnal Filsafat in the upcoming volume, and reasonable effort should be made to remove all references to this article.